PERLINDUNGAN HUKUM BAGI PENERIMA HIBAH ATAS SENGKETA BENDA YANG DIHIBAHKAN MENURUT KUH PERDATA - Grace Ave Maria Wera, Angela; Aditya Pramana Putra, Made (Kertha Negara : Journal Ilmu Hukum, 2025)
The purpose of this study is to analyze legal protection for grant recipients from the perspective of the Civil Code and determine the legal consequences that occur if one of the parties violates the conditions determined by law as a condition for the validity of the agreement. This study uses normative legal research methods with a statutory and analytical approach. The study results show that grants as unilateral agreements do not provide equal legal protection between the grantor and the grantee. Thus, if a grant is declared to have been damaged in the implementation of the grant agreement which gives rise to a dispute, through a court decision must be declared null and void. Key Words: Legal Protection, Donation, Terms of Agreement, Dispute, Null and Void.